Utilização da cinza de folha de cana-de-açúcar como material pozolânico em matrizes cimentantes - Moraes, João Cláudio Bassan de [UNESP] (2015)
Portland cement is widely used in building construction, and one of the mostly materials used in the world. However, Portland cement production generates huge amount of CO 2, and, consequently, researches for alternative materials in building construction is growing up. Another problem is related to growth of sugarcane production in Brazil. Sugar cane straw is a byproduct of harvesting sugar cane, and one of its qualities is the calorific value for power generation that can be compared to sugar cane bagasse. However, the production of energy from burning sugar cane straw generates a waste, the sugar cane straw ash. The residue is the maing element in this work, aiming its use as pozzolanic material in cementitious binder replacing partially the Portland cement. In this work, is studied since the production of this ash until this use in cementing matrices. First, the method of obtaining a good ash with pozzolanic qualities is studied. Therefore, furnaces are used to burn the straw and obtain the ash, then it passes through sieves, and finally grinding the material. After obtaining the ash, it is characterized from Chemical Composition, X-Ray Diffraction, Particle Size, Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis and Scanning Electron Microscopy. Then, after characterizing the ash, it is assessed in cement pastes/pozzolan and lime/pozzolan to evaluate their pozzolanic reactivity. Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis and Scanning Electron Microscopy are used to evaluate the development of pozzolanic reaction. Finally, the ash is used in mortars replacing partially in mass the Portland cement to evaluate the mechanical properties. Four different substitutions were assessed and were compared to the control with no sugarcane straw ash. Results from characterization of sugar cane straw ash and pastes, as well as mechanical properties of mortars, show ...